Interplay Between Microbial Pathogenesis and Pharmacological Management in Congenital Heart Disease: A Narrative Review of Mechanisms, Microbiome Dysbiosis, and Therapeutic Prospects - Salman Mahdey, Aliaa; Jaafar Mohammed, Ali; Sameir, Mohammed (Hammurabi Journal of Medical Sciences, 2025)
Cardiovascular diseases (CVDs) remain the foremost global cause of mortality, with congenital heart disease (CHD) representing the most prevalent birth defect and a major contributor to childhood morbidity and mortality. Beyond structural abnormalities, CHD pathophysiology involves dynamic interactions between host genetics, immune dysregulation, and microbial imbalance. Emerging evidence highlights the role of the gut and oral microbiota in modulating inflammation, metabolism, and therapeutic responses, particularly in neonates with critical CHD (CCHD). This review explores the mechanistic links between microbial pathogenesis and pharmacological management in CHD, emphasizing microbiome-mediated effects on cardiovascular pathology and drug efficacy. A narrative literature of eligible studies addressed microbial alterations, infection risks, or pharmacological interventions in CHD or CVD. Data were synthesized thematically into microbial pathogenesis, early-life microbiome dysbiosis, and drug–microbiota interactions. Microbial agents including Chlamydia pneumoniae, Helicobacter pylori, and cytomegalovirus—are implicated in atherogenesis and endothelial dysfunction. In neonates with CCHD, gut dysbiosis is characterized by Enterococcus and Clostridium overgrowth, depletion of Bifidobacterium and Lactobacillus, and enrichment of temperate phages. These microbial shifts correlate with suppressed amino acid and vitamin metabolism, elevated arachidonic acid derivatives, and systemic inflammation, contributing to poor surgical outcomes. Pharmacologically, several cardiovascular drugs such as statins, ACE inhibitors, ARBs, and beta-blockers modulate microbial composition, influencing drug absorption, metabolism, and therapeutic response. Conversely, microbial enzymes can inactivate key drugs like digoxin and alter warfarin efficacy, underscoring the bidirectional interplay between pharmacotherapy and the microbiome. CHD represents a complex intersection of developmental, microbial, and pharmacological determinants. Targeting microbiome imbalance through precision pharmacotherapy, probiotics, and prebiotic interventions offers a promising avenue to improve clinical outcomes. Future work integrating genomics, metabolomics, and microbiome profiling will be essential to achieve personalized cardiovascular medicine and restore host–microbe homeostasis in CHD patients.